On air blowing direction in the blown bubble-spinning - LI,Zheng-Biao (2014)
This paper studies the effect of airflow direction on morphology of the nanofibers obtained by the blown bubble-spinning, a kind of Bubbfil spinning processes. Regenerated silk fibroin is used in the experiment, and the results indicate that nanofibers with random array structure can be obtained when the blowing air direction is perpendicular to the direction of bubble ejection. While uniform oriented fiber bundles composed of superfine fibers are obverse when the blowing air directs to the bubble ejection. The paper reveals that blowing air direction can be used to control morphology and structure of fibers during the spinning process.